SAT0427 Multicentric Osteoarthritis Intervention Study with Sysadoa (MOVES): Effects of Combined Glucosamine Hydrochloride and Chondroitin Sulfate VS Celecoxib for Painful Knee Osteoarthritis. (10th June 2014) - Hochberg, M.; Martel-Pelletier, J.; Monfort, J.; Möller, I.; Castillo, J.-R.; Arden, N.; Berenbaum, F.; Conaghan, P.; Pap, T.; Richette, P.; Sawitzke, A.; du Souich, P.; et al.
Abstract : Background: Combined glucosamine hydrochloride (GH) and chondroitin sulfate (CS) was found to be efficacious compared with placebo in subjects with knee osteoarthritis (OA) with severe pain in the GAIT trial 1 . The proportion of OA patients who achieved after 6 months a 20% improvement in pain was similar between GH+CS and Celecoxib (CE) 200mg. Objectives: To extend the findings of GAIT, a clinical trial was designed to assess whether GH+CS has comparable efficacy to CE to reduce severe pain in knee OA patients after 6 months of treatment. Secondary objectives included comparison of other outcomes related to signs and symptoms of knee OA and to tolerability and safety. Methods: MOVES was an international multicentric, phase IV, double-blind, non-inferiority, randomized trial to compare efficacy and safety of combined GH+CS (Droglican®, Bioiberica) vs CE in patients with knee OA with severe pain. Patients received either 2 capsules of Droglican (GH250mg and CS200mg) TID or CE200mg and 5 placebo capsules. Patients were eligible if ≥40years, fulfilled the ACR criteria for knee OA, had KL grade 2 or 3 and WOMAC pain>301 (0-500scale). Patients with gastrointestinal or cardiovascular risk were excluded. The primary outcome was the mean decrease in WOMAC Pain after 6 months. Results: 763 patients were screened, 606 randomized to receive GH+CS (N=304) or CE (N=302), 522 (86.1%) completed the trial and included in the PP non-inferiority analysis. There was no difference in proportion completing between groups. Mean (SD) age was 62.7 (8.9) years, 438(83.9%) were women; KL grade 2 was present in 327 (62.6%). The mean WOMAC pain at randomization was 372.0 (41.8) in GH+CS and 370.6 (41.4) in CE. At 6 months, pain decreased ∼50% in both groups to 185.8 (7.4) in GH+CS and 184.7 (7.6) in CE, SEM difference of 1.11 (10.63) units (95%CI-21.99, 19.76) (p=0.917) respecting non-inferiority margin. These results were robust in sensitivity analyses using the ITT population and BOCF imputation in PP and ITT populations. There was no difference in secondary outcomes after the 6-month treatment with WOMAC stiffness of 69.1 (3.0) and 65.8 (3.0) (p=0.434), WOMAC function of 617.0 (23.5) and 595.8 (24.1) (p=0.53), VAS pain of 37.9 and 37.6 (p=0.924) and OMERACT-OARSI responders of 79.7% and 79.2% (p=0.908) in GH+CS and CE groups respectively. Both arms elicited a reduction>50% in joint swelling (p=0.53) and effusion (p=0.61). Overall, there was similar rescue medication consumption in both arms. There was no significant difference in the proportion of patients with treatment-emergent AEs between groups (50.7% overall); no deaths occurred. All the results are consistent with those from the GAIT. Conclusions: The MOVES demonstrated clinical efficacy of a combination of GH and CS and good safety profile in the symptomatic treatment of patients with severe knee OA. References: N Engl J Med 2006Feb23;354(8):795-808 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4950